Quantum well intermixing in GaInNAs/GaAs structures - Sun, Handong (2009)
We report on the characteristics of quantum well intermixing in GaInNAs/GaAs structures of differing N content. Rapid thermal annealing combined with SiO2 caps deposited on the surface of the samples is used to disorder 1.3 mum GaInNAs/GaAs multiquantum wells which have been preannealed in-situ to the stage of blueshift saturation. The different effects of two capping layer deposition techniques on the interdiffusion of In-Ga have been compared, particular regarding the role of sputtering processes. The dependence of quantum well intermixing-induced photoluminescence blueshift on N concentration has provided extra information on the intrinsic properties of the GaInNAs/GaAs material system. We found that the blueshift decreases as the N concentration increases. This finding not only rules out the possible mechanism of N-As interdiffusion, but also demonstrates the alloy stability of GaInNAs due to the strong bond between In-N.